Akkermansia muciniphila: a potential candidate for ameliorating metabolic diseases - Niu, Huifang; Zhou, Minfeng; Zogona, Daniel; Xing, Zheng; Wu, Ting; Chen, Rui; Cui, Dandan; Liang, Fengxia; Xu, Xiaoyun (Frontiers in Immunology, 2024)
Metabolic diseases are comprehensive disease based on obesity. Numerous cumulative studies have shown a certain correlation between the fluctuating abundance of Akkermansia muciniphila and the occurrence of metabolic diseases. A. muciniphila, a potential probiotic candidate colonized in the human intestinal mucus layer, and its derivatives have various physiological functions, including treating metabolic disorders and maintaining human health. This review systematically explicates the abundance change rules of A. muciniphila in metabolic diseases. It also details the high efficacy and specific molecules mechanism of A. muciniphila and its derivatives in treating obesity, type 2 diabetes mellitus, cardiovascular disease, and non-alcoholic fatty liver disease.